2020
DOI: 10.1002/jnr.24757
|View full text |Cite
|
Sign up to set email alerts
|

Corneal nonmyelinating Schwann cells illuminated by single‐cell transcriptomics and visualized by protein biomarkers

Abstract: The cornea is the most innervated tissue in the human body. Myelinated axons upon inserting into the peripheral corneal stroma lose their myelin sheaths and continue into the central cornea wrapped by only nonmyelinating corneal Schwann cells (nm‐cSCs). This anatomical organization is believed to be important for central vision. Here we employed single‐cell RNA sequencing (scRNA‐seq), microscopy, and transgenics to characterize these nm‐cSCs of the central cornea. Using principal component analysis, uniform ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…3a ) were identified using well-established Schwann cell markers (Fig. 3b ) 17 , 27 . This analysis identified myelinating Schwann cells (SC-Myel), nonmyelinating Schwann cells (SC-Nonmyel), proliferating Schwann cells (SC-Prolif), Schwann cells additionally expressing genes typical for endothelial cells (SC-EC) or fibroblasts (SC-FB) and the previously described repair-like, profibrotic keloidal Schwann cells (SC-Keloid) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a ) were identified using well-established Schwann cell markers (Fig. 3b ) 17 , 27 . This analysis identified myelinating Schwann cells (SC-Myel), nonmyelinating Schwann cells (SC-Nonmyel), proliferating Schwann cells (SC-Prolif), Schwann cells additionally expressing genes typical for endothelial cells (SC-EC) or fibroblasts (SC-FB) and the previously described repair-like, profibrotic keloidal Schwann cells (SC-Keloid) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Subset clusters expressing marker genes typical for melanocytes were removed. Schwann cells were characterized by the expression of established marker genes 17 , 27 . Differentially expressed genes were defined as genes displaying an average fold change >2.…”
Section: Methodsmentioning
confidence: 99%
“…A similar approach was applied to the ocular anterior segment in mouse, leading to identification of a novel marker for stem and early transit amplifying cells, TXNIP [ 14 ]. While this work was under review, two studies reported the single cell transcriptomic analysis of human limbal basal epithelium [ 15 ] and murine corneal non-myelinating Schwann cells [ 16 ]. Our study complements and expands these published data by providing a comprehensive single cell atlas of the whole developing and adult human cornea and adjacent conjunctiva that defines their development, limbal progenitor cells and their interactions with immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…As the main goals of our study were the in-depth analysis of Schwann cells in the different scar types and their comparability across different single cell data sets, we next recalculated the combined integrated Schwann cell cluster, removed all melanocytes and performed subclustering (Figure 2). The different Schwann cell subclusters (Figure 2a) were identified using well-established Schwann cell markers (Figure 2b) 31,41 . This analysis identified myelinating Schwann cells (SC-Myel), nonmyelinating Schwann cells (SC-Nonmyel), proliferating Schwann cells (SC-Prolif), Schwann cells additionally expressing genes typical for endothelial cells (SC-EC) or fibroblasts (SC-FB) and the previously described repair-like, pro-fibrotic keloidal Schwann cells (SC-Keloid) (Figure 2a and b).…”
Section: Resultsmentioning
confidence: 99%
“…Subset clusters expressing marker genes typical for melanocytes were removed. Schwann cells were characterized by the expression of established marker genes 31,41 . Differentially expressed genes were defined as genes displaying an average fold change > 2.…”
Section: Methodsmentioning
confidence: 99%